Effects of inspiratory muscle training on exercise responses in Paralympic athletes with cervical spinal cord injury - West, C. R.; Taylor, B. J.; Campbell, I. G.; Romer, L. M. (Scandinavian Journal of Medicine & Science in Sports, 2014)
We asked whether specific inspiratory muscle training (IMT) improves respiratory structure and function and peak exercise responses in highly trained athletes with cervical spinal cord injury (SCI). Ten Paralympic wheelchair rugby players with motor-complete SCI (C5-C7) were paired by functional classification then randomly assigned to an IMT or placebo group. Diaphragm thickness (B-mode ultrasonography), respiratory function [spirometry and maximum static inspiratory (PI,max) and expiratory (PE,max) pressures], chronic activity-related dyspnea (Baseline and Transition Dyspnea Indices), and physiological responses to incremental arm-crank exercise were assessed before and after 6 weeks of pressure threshold IMT or sham bronchodilator treatment. Compared to placebo, the IMT group showed significant increases in diaphragm thickness (P = 0.001) and PI,max (P = 0.016). There was a significant increase in tidal volume at peak exercise in IMT vs placebo (P = 0.048) and a strong trend toward an increase in peak work rate (P = 0.081, partial eta-squared = 0.33) and peak oxygen uptake (P = 0.077, partial eta-squared = 0.34). No other indices changed post-intervention. In conclusion, IMT resulted in significant diaphragmatic hypertrophy and increased inspiratory muscle strength in highly trained athletes with cervical SCI. The strong trend, with large observed effect, toward an increase in peak aerobic performance suggests IMT may provide a useful adjunct to training in this population.